The effect of cannabis edibles on driving and blood THC - S Zhao; B Brands; P Kaduri; C.M Wickens; O.S.M Hasan; S Chen; B Le Foll; P Di Ciano (BMC, 2024)
Abstract Background Cannabis has been shown to impact driving due to changes produced by delta-9-tetrahydrocannabinol (THC), the psychoactive component of cannabis. Current legal thresholds for blood THC while driving are based predominantly on evidence utilizing smoked cannabis. It is known that levels of THC in blood are lower after eating cannabis as compared to smoking yet the impact of edibles on driving and associated blood THC has never been studied. Methods Participants drove a driving simulator before and after ingesting their preferred legally purchased cannabis edible. In a counterbalanced control session, participants did not consume any THC or cannabidiol (CBD). Blood was collected for measurement of THC and metabolites as well as CBD. Subjective experience was also assessed. Results Participants consumed edibles with, on average, 7.3 mg of THC, which is less than the maximum amount available in a single retail package in Ontario, providing an ecologically valid test of cannabis edibles. Compared to control, cannabis edibles produced a decrease in mean speed 2 h after consumption but not at 4 and 6 h. Under dual task conditions in which participants completed a secondary task while driving, changes in speed were not significant after the correction for multiple comparison. No changes in standard deviation of lateral position (SDLP; 'weaving'), maximum speed, standard deviation of speed or reaction time were found at any time point or under either standard or dual task conditions. Mean THC levels were significantly increased, relative to control, after consuming the edible but remained relatively low at approximately 2.8 ng/mL 2 h after consumption. Driving impairment was not correlated with blood THC. Subjective experience was altered for 7 h and participants were less willing/able to drive for up to 6 h, suggesting that the edible was intoxicating. Interpretation This is the first study of the impact of cannabis edibles on simulated driving. Edibles were intoxicating as revealed by the results of subjective assessments (VAS), and there was some impact on driving. Detection of driving impairment after the use of cannabis edibles may be difficult.